A Case Study on Occupational Safety and Health Management in Heveaboard Sdn. Bhd., a Subsidiary of Heveawood Industries Sdn. Bhd., Gemas, Negeri Sembilan Darul Khusus - Employers' and Employees' Interpersonal - Ong, Kau Liong (1998)
A three months research was conducted on Occupational Management in Heveaboard Sdn. Bhd. a subsidiary of Heveawood in Gemas, Negeri Sembilan Darul Khusus. Interviews were conducted and some valuable information received. The subject matter includes the identification of the product, the product process, safety administration of HBSB, HBSB's safety situation, identifying the main issues of the company, analysis of the problem, and finally, recommendations for HBSB's safety and health.